Multimedia Development Flash Calistung Through the Introduction of Animals for Elementary School Students - Nor Saleha; Endang Purwaningsih; Riska Pristisni (Postgraduate, University of Mataram, 2023)
In the learning process, the use of media in learning becomes one that must be used and utilized by teachers, because Learning media has a very important role, by using the teaching and learning process media makes it easier for students to understand a material that will be conveyed. The material presented is mainly for Grade I elementary school students in reading, writing and calculating the beginning (Calistung) contained in the learning of Indonesian language and mathematics. Researchers develop multimedia flash corresponding analysis of student needs. The purpose of this research is to develop flash multimedia as a learning media focusing on reading, writing and counting exercises, and this multimedia makes students more practical, and effective in improving students ' Calistung skills. This research method uses R & D with Lee & Owens model which has 5 stages (analysis, design, development, implementation, and evaluation stage). The subjects of this study were first grade students of SDN Jatimulyo 5 as an experimental class and SDN Sukun 3 Malang control, with a total of 20 students in field trials. The results showed that the validity of multimedia multimedia products 83.1%, the practicality of teacher users 91.6%, the practicality of students 95.8%, and the effectiveness of using the Test Independent Sample t-Test GIS (2-tailed) of 0.034 is smaller than the significant level set at 0.05. Based on the results obtained, it can be concluded that flash multimedia can be developed as a learning medium, in Indonesian and mathematics subjects that focus on reading, writing and counting Grade I elementary school students in improving the ability to read, write and count beginning